My Son Fred Living with Autism : How Could You Manage? I Couldn't. I Did It Anyway. - Deckmar, Maud, 1951- (Jessica Kingsley Publishers, 2004)
Maud Deckmar tells a touching and honest story of living with Fred, her eldest child, who has autism and an intellectual disability. She recounts here the great struggles and sorrows as well as the love and happiness she has experienced from his early childhood to adulthood. She vividly describes the feelings of grief after Fred's diagnosis, the sense of loss when old friends distance themselves and the pervasive feelings of guilt about putting her son into care and admitting that she can no longer cope. She stresses the importance of communication and cooperation between parents and carers, a.